Arsenic exposure and cancer risk reduction with local ordinance requiring whole-house dual-tank water treatment systems. Issue 5 (4th July 2018) - Rockafellow-Baldoni, Megan; Spayd, Steven E.; Hong, Jun-Yan; Meng, Qingyu; Ohman-Strickland, Pamela; Robson, Mark G.
ABSTRACT: Arsenic, a known human carcinogen, occurs naturally in groundwater in New Jersey and many other states and countries. A number of municipalities in the Piedmont, Highlands, and Valley and Ridge Physiographic Provinces of New Jersey have a high proportion of wells that exceed the New Jersey maximum contaminant level (MCL) of 5 µg/L. Hopewell Township, located in Mercer County and the Piedmont Province, has a progressive local ordinance which requires the installation of dual-tank, point-of-entry treatment systems on affected wells. This provided a unique study opportunity. Of the 55 homes with dual-tank POE treatment systems recruited into this study, 51 homes (93%) had arsenic levels under the MCL at the kitchen sink, regardless of years in service and/or maintenance schedule adherence. Based on the study participants' water consumption and arsenic concentrations, we estimate that Hopewell's arsenic water treatment ordinance, requiring POE dual-tank arsenic treatment, reduced the incidence of excess lifetime (70-year) bladder and lung cancers from 121 (1.7 cancer cases/year) to 16 (0.2 cancer cases/year) preventing 105 lifetime cancer cases (1.5 cases/year). Because the high risk of cancer from arsenic can be mitigated with effective arsenic water treatment systems, this ordinance should be considered a model for other municipalities.